2004
DOI: 10.1128/iai.72.1.106-113.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation of Lipooligosaccharides Promotes Biofilm Formation by Nontypeable Haemophilus influenzae

Abstract: Nontypeable Haemophilus influenzae (NTHi) is a major cause of opportunistic respiratory tract infections, including otitis media and bronchitis. The persistence of NTHi in vivo is thought to involve bacterial persistence in a biofilm community. Therefore, there is a need for further definition of bacterial factors contributing to biofilm formation by NTHi. Like other bacteria inhabiting host mucosal surfaces, NTHi has on its surface a diverse array of lipooligosaccharides (LOS) that influence host-bacterial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
132
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 69 publications
9
132
1
Order By: Relevance
“…More detailed analysis by scanning electron microscopy showed dense multilayered bacterial communities (Fig. 5C) that are reminiscent of those observed by our group and others in vitro (12,38,43,48).…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…More detailed analysis by scanning electron microscopy showed dense multilayered bacterial communities (Fig. 5C) that are reminiscent of those observed by our group and others in vitro (12,38,43,48).…”
Section: Resultsmentioning
confidence: 51%
“…Moreover, prior work has clearly shown that NeuAc promotes biofilm formation and bacterial persistence in animal models of NTHi disease (4,18,43). Our previous studies did not show any biofilm phenotype associated with loss of PCho, at least in terms of initial attachment or numbers of viable bacteria found within biofilms (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that NTHi biofilm formation on epithelia requires matrix formation and the ability to incorporate sialic acid into the biofilm, as suggested by previous studies (6,7). To test this hypothesis, NTHi 2019siaA, 2019siaB, and 2019wecA were cocultured on airway epithelia.…”
Section: Resultsmentioning
confidence: 99%
“…Haemophilus influenzae (NTHi) has recently been shown to form biofilms in vitro and in otitis media (OM) (6)(7)(8)(9)(10); however, there is no information on NTHi biofilm formation in the lung or in CF.…”
mentioning
confidence: 99%